2010
DOI: 10.1177/1087054710370935
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction in School-Age Children With ADHD

Abstract: As a group, children with ADHD displayed more problems on neuropsychological measures of EF than non-clinical children; at the individual level, there appeared to be heterogeneity in EF impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 34 publications
5
68
1
14
Order By: Relevance
“…Y siete (50%) de los 14 estudios que analizaron la TD bajo incertidumbre (Antonini, Becker, Tamm, y Epstein, 2015;Geurts, Van der Oord, & Crone, 2006;Hovik et al, 2015;Lambek et al, 2011;Masunami, Okazaki y Maekawa, 2009;Skogli, Egeland, Andersen, Hovik y Oie 2013;Skogli, Andersen, Hovik, y Oie 2014) no encontraron evidencias de diferencias en el desempeño de los niños y adolescentes con TDAH y los niños del grupo control.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Y siete (50%) de los 14 estudios que analizaron la TD bajo incertidumbre (Antonini, Becker, Tamm, y Epstein, 2015;Geurts, Van der Oord, & Crone, 2006;Hovik et al, 2015;Lambek et al, 2011;Masunami, Okazaki y Maekawa, 2009;Skogli, Egeland, Andersen, Hovik y Oie 2013;Skogli, Andersen, Hovik, y Oie 2014) no encontraron evidencias de diferencias en el desempeño de los niños y adolescentes con TDAH y los niños del grupo control.…”
Section: Resultsunclassified
“…En sentido contrario, el 75% (6 de 8) de los estudios que trabajaron con muestras mixtas de niños y de adolescentes no encontraron diferencias en las medias de los desempeños de ambos grupos (Hovik et al, 2015;Lambek et al, 2011;Masunami et al, 2009;Scheres et al, 2006;Skogli et al, 2014;Skogli et al, 2013). Y la totalidad de los estudios (3) que analizaron sólo el desempeño en adolescentes (Kroyzer et al, 2014;Pollak y Shoham, 2015;Toplak et al, 2005), encontraron evidencias de un desempeño inferior de los jóvenes con TDAH.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Since the approach adopted in this instrument refers to behavioral assessment and conducted using structured observation of parents, it does not suffer from traditional performance instruments such as the continuous performance test (17,26), the Wechsler cancellation sub-test and the NEPSY-II visual attention sub-test. The administration of this instrument is less time consuming compared with performance tests.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that (i) the ADHD abnormalities persisted into adulthood, and (ii) these abnormalities arose from the atypical functioning of corticocerebellar and corticostriatal timing circuits (see also Coull and Nobre, 2008;Smith et al, 2008;Terry et al, 2009). A plethora of neuropsychological evidence indicates that abnormalities in executive functioning, particularly with regard to behavioural inhibition, are dysfunctional in in ADHD (Barkley, 1997;Chamberlain et al, 2010;Lambek et al, 2011;Mattison and Mayes, 2012). Arendts et al (2010) have presented evidence of visual cortex abnormalities in adults with ADHD, using voxel-based morphometry of high resolution MRI scans, that may be related to impairments in early-stage, "subexecutive" attentional mechanisms.…”
Section: Introductionmentioning
confidence: 99%